Efektivitas Penggunaan E-Commerce dalam Perkembangan Usaha Kecil Menengah di Kota Surakarta - Nugraha, Arjun Anugrah (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
There are many factors that influence the development of MSMEs in Indonesia among ecommerce users. In this regard, researchers will examine the influence of businesses with e-commerce content on retail businesses on the marketing aspects of micro, small and medium enterprises in the city of Surakarta. The specific objectives of this research are 1). To help retail business managers maximize product distribution, information and socialization so that they are easily accessible to the community so they can compete with business managers using e-commerce media. 2). socialization process, product education, marketing and product data processing through e-commerce. As for the research results, there is a significant influence of e-commerce media on the development of MSMEs in the city of Surakarta..